Acehnese traditional clothing recognition based on augmented reality using hybrid tracking method - Ahmad Ihsan; Nurul Fadillah; Chicha Rizka Gunawan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Aceh's traditional clothing is cultural heritage in Indonesia. In today's, the problem faced is the lack of media to introduce cultural heritage in Aceh. Therefore was formed a media which could recognition Acehnese traditional clothing using Augmented Reality technology. Augmented Reality technology is used to users can add virtual objects to real environments. In this research, the method used is the Hybrid Tracking method, a Hybrid Tracking method is a combination tracking system of two or more tracking techniques, hybrid tracking is used to get a better tracking system and to get tracking speeds based on better distances. The results showed that the reading of markers by the cameras was greatly influenced by distance, light intensity, marker angle, and size of the device's RAM. The closest distance from the marker to the camera that can display 3D objects is 20 cm while the farthest distance cannot display 3D objects is 100 cm. And the angle of reading the marker is only around 0° an angle of 45°. The average distance that can detect markers is 0.5 m, the average time that can be detected is 0.068 sec, and the average speed obtained is 7.505 m / sec.